(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Nephrotoxicity poses a significant health challenge, warranting innovative approaches for its management. The leaves of Adhatoda cordifolia (A. cordifolia) and the leaves of Cyathea gigantea (C. gigantea) were meticulously collected from their natural habitats and authenticated by Dr. S. N. Dwivedi, a distinguished authority in botanical sciences. The authentication process ensured the accuracy of plant species identification, enhancing the credibility of subsequent investigations. To harness the therapeutic potential of these plants, a meticulous extraction process was employed. Leaves and seeds of the chosen plants were meticulously gathered, shade-dried to preserve their active constituents, and then processed into a coarse powder using a mechanical grinder. The powdered material underwent filtration through a No. 40 filter, facilitating the separation of coarse particles while retaining essential components.